Physical and transition risk premiums in euro area corporate bond markets - Joost Victor Bats; Giovanna Bua; Daniel Kapp (European Central Bank (ECB), 2024)
The European Union plays a prominent role in climate regulations initiatives, this commitment likely implies that climate risk premiums look different in Europe compared to the rest of the world. This paper examines the pricing implications of climate risks in euro area corporate bond markets, focusing on physical and transition risk. Using climate news as a gauge for systematic climate risk, we find a significant pricing effect of physical risk in long-term bonds, with investors demanding higher returns on bonds exposed to physical risk shocks. The estimated physical risk premium is 34 basis points, indicating increased awareness and hedging demand after the Paris Agreement. Transition risk premiums are smaller and less significant, reflecting the ongoing transition to a low-carbon economy. Our findings contribute to understanding climate risk pricing in the European bond markets, highlighting the importance of physical risk and the evolving nature of investor demand for climate-resilient assets.
Keywords: G12; G14; G28; Q51; Q54; 330; Climate physical risk; climate transition risk; corporate bonds; news index; intertemporal hedging demand